2006
DOI: 10.1007/s10750-006-0231-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of genes expressed in regenerating intestine and non-eviscerated intestine of Apostichopus japonicus Selenka (Aspidochirotida: Stichopodidae) and cloning of ependymin gene

Abstract: The regeneration of the intestine of sea cucumber (Apostichopus japonicus) was studied by describing historically the changes that occurred during intestine regeneration on the fifth day after chemicallyinduced evisceration. An expressed sequence tag (EST) analysis was undertaken to identify major genes, which might be involved in intestine regeneration of A. japonicus. Two cDNA libraries were constructed with directional cloning method, one for regenerating intestine collected on the third, fourth and fifth d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…japonicas) [68]. In the current study, both C3 and C3-2 in albino intestine were found to be down-regulated.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 55%
“…japonicas) [68]. In the current study, both C3 and C3-2 in albino intestine were found to be down-regulated.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 55%
“…NADH dehydrogenase was taken as a reference gene to normalize gene expression data, based on a previous investigation [7], [16], [22], [30]. All primers were tested to be effective on PCR amplication.…”
Section: Resultsmentioning
confidence: 99%
“…Thermal cycling was as follows: (1) 95°C for 5 s; (2) 40 cycles at 95°C for 10 s, 60°C for 20 s and 72°C for 30 s. The melting curve analysis of the amplification products was done to demonstrate the specificity of the PCR products. NADH dehydrogenase (NADHF, NADHR, Table S1) was used as a housekeeping gene for internal standardization [7], [16], [22], [30]. The 2−△△CT method was used to analyze the expression level.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, many genes show differential expression during intestinal regeneration (Ortiz-Pineda et al, 2009). However, only a few genes playing important roles in intestinal regeneration in sea cucumbers have been thoroughly studied, such as Wnt9, Bmp1, ependymin, serum amyloid A, survivin, and mortalin (Santiago-Cardona et al, 2003;Suarez-Castillo et al, 2004;Zheng et al, 2006;Mashanov et al, 2010Mashanov et al, , 2012. Therefore, the molecular and genetic basis of intestinal regeneration still needs further study.…”
Section: Introductionmentioning
confidence: 99%